ANALISIS SISTEM ANTRIAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BANDUNG: STUDI PADA LOKET PELAYANAN PENCATATAN DAN PENERBITAN AKTA KELAHIRAN BAYI BERUMUR 0-60 HARI - Riana Sinaga; Devilia Sari (Center for Economic Studies Universitas Katolik Parahyangan, 2015)
A long queue is one cause of service dissatisfaction. This problem is also faced by the Population and Registry Office of Bandung City, specificaly in the listing and publishing of birth certificates infants aged 0-60 days old. In this study, researchers tried to analyze the current queue system of this service and proposed several queue systems to increase the service rate. This study shows that the service provided by the Population and Registry Office is not optimal. It can be seen from the average number in the queue (and average number in the system (, namely, 22.09 and 23.05 people, respectively. Other evidences are average time in queue and average time in system, which are 95.4 minutes and 99.6 minutes, respectively. The best queue system that can be implemented by the office is single channel multi phase. Keywords: Queue system, public service, queue model.